The Role Of Mahmudkho’ja Behbudiy In The Activity Of The Jadid Schools (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the contribution of the Jadid reformer and enlightener Mahmudkho’ja Behbudiy to the establishment and development of new- method (usul-i jadid) schools in Turkestan in the early twentieth century. Drawing on Behbudiy’s own pedagogical and publicistic works, the study reconstructs the two- stage structure and year-by-year curriculum of his school, the system of annual public examinations, the textbooks he authored, and his broader vision of education as the foundation of national progress. The article shows that, despite the resistance of both the tsarist colonial administration and the conservative clergy, Behbudiy turned the new-method school into an instrument for training a modern, secularly and religiously literate generation in Turkestan.
Keywords: Mahmudkho’ja Behbudiy; Jadidism; usul-i jadid school; Turkestan; educational reform; textbook; curriculum; enlightenment; native-language instruction